Barriers to Leadership: Experiences of Women Leaders in Business and Politics - Martha Isabel Lasso Quintero; Heriberto Galeano Trilleras; Mabel Concepción Valencia Mosquera (Revista CEA)
Objective: This study aimed to explore the challenges women face when exercising leadership in the political and business spheres in the department of Cauca, Colombia.